![](https://rs.olm.vn/images/avt/0.png?1311)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
![](https://rs.olm.vn/images/avt/0.png?1311)
\(\left(x-2\right)\left(2x+1\right)-5\left(x+3\right)=2x\left(x-3\right)+4\left(1+2x\right)-2\left(1+x\right)\)
\(2x^2+x-4x-2-5x-15=2x^2-6x+4+8x-2-2x\)
\(x-4x-2-5x-15=-6x+4+8x-2-2x\)
\(\Rightarrow-8x-17=2\)
\(-8x=19\Rightarrow x=-\dfrac{19}{8}\)
Vậy \(x=-\dfrac{19}{8}\)
![](https://rs.olm.vn/images/avt/0.png?1311)
Ta có : 2x - 37 = (2x + 1) - 38
Do 2x + 1 \(⋮\)2x + 1
Để (2x + 1) - 38 \(⋮\)2x + 1 thì 38 \(⋮\)2x + 1 => 2x + 1 \(\in\)Ư(38) = \(\left\{\pm1;\pm2;\pm19;\pm38\right\}\)
Lập bảng :
2x + 1 | 1 | -1 | 2 | -2 | 19 | -19 | 38 | -38 |
x | 0 | -1 | ko thõa mãn | không thõa mãn | 9 | -10 | ko thõa mãn | ko thõa mãn |
Vậy x = {0; -1; 9; -10} thì (2x - 37) \(⋮\)2x + 1
![](https://rs.olm.vn/images/avt/0.png?1311)
\(27-\left(2x+1\right)=4\)
\(2x+1=27-4\)
\(2x+1=23\)
\(2x=23-1\)
\(2x=22\)
\(x=22:2\)
\(x=11\)
Vậy x = 11
#HQX
![](https://rs.olm.vn/images/avt/0.png?1311)
\(GIẢI\)
\((\frac{9}{2}-2x)\times\frac{-11}{7}=\frac{11}{14}\)
\(\frac{9}{2}-2x=\frac{11}{14}:\frac{-11}{7}\)
\(\frac{9}{2}-2x=\frac{-1}{2}\)
\(2x=\frac{9}{2}-(\frac{-1}{2})\)
\(2x=5\)
\(x=5:2\)
\(x=2,5\)
![](https://rs.olm.vn/images/avt/0.png?1311)
<=> 2x^2 +x-4x-2-5x-15=2x^2-6x+4+8x-2-2x
2x^2-8x-17-2x^2-2=0
-8x-19=0
x=-19/8
![](https://rs.olm.vn/images/avt/0.png?1311)
\(3x\left(2x+1\right)=0\)
\(\Rightarrow\orbr{\begin{cases}2x+1=0\\3x=0\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}2x=-1\\x=0\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=-\frac{1}{2}\\x=0\end{cases}}\)
\(\frac{\frac{6}{5}+\frac{6}{35}-\frac{6}{125}-\frac{6}{2009}-\frac{6}{2011}}{\frac{7}{5}+\frac{7}{35}-\frac{7}{125}-\frac{7}{2009}-\frac{7}{2011}}\)
\(=\frac{6.(\frac{1}{5}+\frac{1}{35}-\frac{1}{125}-\frac{1}{2009}-\frac{1}{2011})}{7.(\frac{1}{5}+\frac{1}{35}-\frac{1}{125}-\frac{1}{2009}-\frac{1}{2011})}\)
\(=\frac{6}{7}\)
Tìm x
\(a,3x(2x+1)=0\)
\(\Rightarrow\hept{\begin{cases}3x=0\\2x+1=0\end{cases}}\)
\(\Rightarrow\hept{\begin{cases}x=0\\x=\frac{-1}{2}\end{cases}}\)
Vậy \(x=0\)hoặc \(x=\frac{-1}{2}\)
\(b.\frac{2}{3}-\frac{1}{3}(x-\frac{3}{2})-\frac{1}{2}(2x+1)=5\)
\(\frac{2}{3}-\frac{1}{3}x+\frac{1}{2}-x-\frac{1}{2}=5\)
\(\frac{2}{3}+\frac{1}{2}-\frac{1}{2}-x(\frac{1}{3}+1)=5\)
\(\frac{4}{3}x=\frac{2}{3}-5\)
\(\frac{4}{3}x=\frac{-13}{3}\)
\(x=\frac{-13}{3}\div\frac{4}{3}\)
\(x=\frac{-13}{4}\)
Chúc ban học tốt
![](https://rs.olm.vn/images/avt/0.png?1311)